Analysis of The Application of Sanctions Against Notaries Who Forgery Deeds of Transferring Land Rights (Study of Supreme Court Decision Number 139 K/Pid/2016) - Nurwansyah, Muhammad Erizal; Rahaditya, R. (Devotion : Journal of Research and Community Service, 2023)
The Law on the Position of Notaries does not regulate the existence of criminal sanctions for the actions of notaries. This does not absolve the notary from criminal liability. Notaries can be held criminally liable if their actions contain a criminal element, where the relevant Notary can be summoned by the Notary Honorary Council. The problem is how to apply legal sanctions to a notary who falsifies the deed transferring land rights in Supreme Court Decision Number 139 k/PID/2016? And what is the responsibility of the Notary who falsified the deed of transferring land rights in Supreme Court Decision Number 139 K/PID/2016? The research method used is normative juridical. The results of the research are that the Notary concerned cannot be held responsible when elements of fraud and error are committed by the parties, because the Notary only records what is conveyed by the parties to be included in the deed, this is often known as partij deed. False information submitted by the parties is the responsibility of the parties. This means that a notary is only responsible if the fraud originates from the wishes and/or desires of a notary. In the UUJN which regulates sanctions for violations committed by a notary, the deed made by a notary does not have the power of an authentic deed but only has the power of a private deed. In relation to the actions of notaries who commit criminal acts of forgery of deeds or criminal acts of false statements committed by parties, the UUJN does not specifically regulate criminal provisions because they are based on the principle of legality which are the principles in the Criminal Code.